Metody analizy ryzyka operacyjnego - Kuziak, Katarzyna (Methods in operational risk analysis, 2006)
Enterprises and financial institutions perceive operational risk as a very dangerous type of risk. Real cases of operational risk (Nomura Bank, BACS, Morgan Grenfell, Enron, WorldCom, Parmalat) cause great interests and many studies on operational risk. In that paper classification of methods in operational risk analysis will be presented, especially in one of the element of the risk process, namely in the risk measurement. In the stochastic modeling approach parameters estimation of severity and frequency distribution might be done by the loss distribution approach. Two examples of the loss distribution approach illustrate issue of the operational risk measurement.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1133, s. 254-265